2013
DOI: 10.1016/j.ygeno.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A 4-gene panel as a marker at chromosome 8q in Asian gastric cancer patients

Abstract: A widely held viewpoint is that the use of multiple markers, combined in some type of algorithm, will be necessary to provide high enough discrimination between diseased cases and non-diseased. We applied stepwise logistic regression analysis to identify the best combination of the 32 biomarkers at chromosome 8q on an independent public microarray test set of 80 paired gastric samples. A combination of SULF1, INTS8, ATP6V1C1, and GPR172A was identified with a prediction accuracy of 98.0% for discriminating car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
0
24
2
Order By: Relevance
“…Limited studies indicate that INTS8 contains mutations in peripheral T cell lymphoma compared with non-malignant samples from 12 patients [36], and a combination of INTS8 with SULF1 , ATP6V1C1 , and GPR172A can be used to discriminate gastric carcinomas from adjacent noncancerous tissues [37]. In this study, we found that, potentially regulated by demethylation (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Limited studies indicate that INTS8 contains mutations in peripheral T cell lymphoma compared with non-malignant samples from 12 patients [36], and a combination of INTS8 with SULF1 , ATP6V1C1 , and GPR172A can be used to discriminate gastric carcinomas from adjacent noncancerous tissues [37]. In this study, we found that, potentially regulated by demethylation (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Of note, we experimentally validated their transcriptional alteration in primary breast and colon tumor samples (Figure 6), confirming TCGA data re-analysis. Interestingly, microarray- and exome sequencing-based studies proposed a role of INTS8 in gastric cancer and peripheral T-cell lymphoma [26,27]. Unfortunately, freely available data from TCGA (tier 1) did not include RNA-Seq data from paired stomach adenocarcinoma (STAD) samples and datasets of peripheral T-cell lymphoma (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, INTS3 was found to be significantly overexpressed in cell lines and tumor tissues from hepatocellular carcinoma (HCC) patients compared with their non-cancerous counterparts [25]. In the last few years, both microarray and exome sequencing analyses have suggested a possible role of INTS8 in gastric cancer and peripheral T-cell lymphoma, respectively [26,27]. Furthermore, INTS14/VWA9 was found to be upregulated in immortalized cells, cancer cells, and non-small-cell lung cancer tissues [28].…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies have been performed to evaluate genetic alterations associated with early GCs (1,2,4,5). Defining the genetic instability aids in the identification of the tumor-specific signatures involved in the initiation and progression of GCs, and thus aids in locating genomic biomarkers for the early detection of GC (5).…”
Section: Introductionmentioning
confidence: 99%
“…Defining the genetic instability aids in the identification of the tumor-specific signatures involved in the initiation and progression of GCs, and thus aids in locating genomic biomarkers for the early detection of GC (5). However, the molecular mechanism of GC development remains to be understood, and identification of the predictive markers in the early stage is crucial.…”
Section: Introductionmentioning
confidence: 99%